Pengaruh Social Media Work Related Use, Strain, Social Related Use, Excessive Use Of Personal Social Media At Work, Terhadap Job Performance Di Super Indo Jakarta - Elang Putri Adiwijaya; Nur Istiqomah; Netania Emilisa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to examine and analyze the variables work related use, strain, social related use, excessive use of personal social media at work, for job performance at Super Indo Jakarta. The sample used in this study amounted to 200 respondents. The sampling technique used was sample random sampling. Data were analyzed using the Structure Equation Model (Quantitative) method. The results of this study are: (1) Work Related Use has a positive effect to Job Performance, (2) Strain has a positive effect to Job Performance, (3) Social Related Use has a positive effect to Job Performance, and (4) Excessive Use of Personal Social Media at Work has a positive effect to Job Performance.